Programa de Manejo das Dunas das Praias de Osório - RS - TABAJARA, LUIZ LIBERATO; MARTINS, LUIZ ROBERTO SILVA; NICOLDI, JOÃO LUIS (Pesquisas em Geociências, 2001)
An intensive and detailed study developed in a pilot area located in the northern portion of Rio Grande do Sul (Brazil) coastal plain, more specifically at Atlântida and Mariápolis resorts, Osório, was carried out in order to establish a dune management program. The study contributes to the beach profile preservation of the studied area and can be divided in three stages: a) diagnosis and mapping; b) dune reconstruction and c) activities aiming at controlling of degradation. For the diagnosis and mapping of the pilot area, aerial survey with small format photographs were taken using a 35-mm camera. The photographs were georeferenced and the images processed through a Geographic Information System – GIS. The technique of dune reconstruction involved replenishment of poor sand delivery areas, stabilization through vegetation profile, reformation of dunes with the aid of machines, and control of wind deflated surfaces through structural methods. Protection of remaining dunes consisted of placing straw tracks ahead of the dune system, detour signals conducting to shoreline transversal to northeast wind and control of erosion through drainage ditches and building of a wall support. Strategic measures were taken to encourage the participation of the population and the support of authorities, and classes on environmental education began to be taught at municipal schools. The basic principle in dune management is to maintain a satisfactory vegetative cover on the foredune, to avoid sand evasion to the continent and its consequent lost from the coastal system. Management of coastal dunes involves the application of sound land use principles, organization of recreational activity and rehabilitation of disturbed dunes.